2007
DOI: 10.1149/1.2753218
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Characterization of Parallel-Plates Electrochemical Reactor

Abstract: This work presents a methodology for characterizing parallel-plates electrochemical reactors, which allows obtaining precise knowledge about the operation of the unit. Flow distribution is analyzed by injecting a dye at the inlet of the reactor and is followed by a digital video-camera. This has produced knowledge about several parameters such as solution mixing in the diffuser, inter-electrode separation (gap) and linear flow velocity in the reaction chamber of the reactor. Residence time distribution was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Various types of experimental studies can be carried out in flow cells to measure them. Some representative examples include: mass transfer characterisation of planar and porous electrodes using the limiting current method 98,99 or reactant conversion method, 100,101 the effect of turbulence promoters, [102][103][104][105][106] effect of manifold flow, 82,107 flow dispersion by conductivity 101,[108][109][110] and dye flow visualisation, [111][112][113][114][115] bubble or particle image velocimetry, 116,117 local potential distribution by probes, [118][119][120] local current distribution by segmented electrodes, 113,121,122 determination of polarisation curves, 98,123 plus the the importance of operational conditions. [124][125][126] A myriad of applications has been explored and commercialised over several decades, making an impact in several fields.…”
Section: Features Of the Plane Parallel Flow Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of experimental studies can be carried out in flow cells to measure them. Some representative examples include: mass transfer characterisation of planar and porous electrodes using the limiting current method 98,99 or reactant conversion method, 100,101 the effect of turbulence promoters, [102][103][104][105][106] effect of manifold flow, 82,107 flow dispersion by conductivity 101,[108][109][110] and dye flow visualisation, [111][112][113][114][115] bubble or particle image velocimetry, 116,117 local potential distribution by probes, [118][119][120] local current distribution by segmented electrodes, 113,121,122 determination of polarisation curves, 98,123 plus the the importance of operational conditions. [124][125][126] A myriad of applications has been explored and commercialised over several decades, making an impact in several fields.…”
Section: Features Of the Plane Parallel Flow Cellmentioning
confidence: 99%
“…For example, an array of 32 circuit boardprinted planar segmented electrodes has permitted the determination of local limiting current density for ferricyanide ion reduction in the laboratory FM01-LC electrolyser, showing that the incorporation of turbulence promoters results in a higher averaged mass transfer and a more uniform current distribution, 121 compared to the non-uniformity near the inlet at unrestricted channels. 113 Similar circuit boardprinted arrays were later implemented in fuel cells. 200 Individually connected stacked meshes 201 and segmented porous electrodes 202 have also been considered, as well as indirect current measurements with magnetic loop arrays.…”
Section: Features Of the Plane Parallel Flow Cellmentioning
confidence: 99%
“…The fluid dynamics analysis of a cell FM01-LC was made by computation fluid dynamics (CFD). Dimensions and geometry of reactor as well as the diffuser are taken from (3). The computer used in the solution was a workstation HP xw6400 model with a Dual Xeon processor at 1.8 GHz.…”
Section: Simulationsmentioning
confidence: 99%
“…The same methodology was use by Velasco et al (3) in FM01-LC cells injecting 0.05 ml of and vegetable ink tracer at the inlet of the reaction chamber, the flow path was filmed by a video camera. The results of Velasco et al (3) and Bengoa et al (1,2) where similar and it was demonstrated that flow in the reaction chamber is asymmetric.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation